Ḥiwālah and Islamic Factoring Revisited : A Maqāṣid al-Sharīʿah–Based Legal Analysis of Debt Transfer in Indonesian Islamic Banking - Hizbullah, Muhammad; Haidir (Tabayyanu : Journal Of Islamic Law, 2025)
Debt transfer mechanisms play an increasingly significant role in contemporary Islamic finance, particularly in addressing liquidity constraints and managing credit risk. In Indonesia, two principal instruments are employed for this purpose: ḥiwālah, a classical Islamic contract of debt transfer, and Islamic factoring, commonly structured through wakālah bil ujrah. Although these mechanisms are often treated as functionally interchangeable in practice and regulation, their doctrinal foundations, legal implications, and ethical orientations differ substantially. This article revisits ḥiwālah and Islamic factoring through a maqāṣid al-sharīʿah–based legal analysis, examining whether current regulatory and institutional practices genuinely reflect the objectives of Islamic law. Using a normative–comparative methodology, the study analyzes classical fiqh literature, Indonesian Sharīʿah fatwas, banking regulations, and relevant civil law provisions on receivables transfer. The article argues that the regulatory convergence of ḥiwālah and Islamic factoring has produced conceptual ambiguity and potential moral hazard, particularly in risk allocation and remuneration structures. It concludes by proposing a reconceptualization of Islamic factoring as a distinct Sharīʿah-compliant commercial instrument, rather than a mere extension of ḥiwālah, in order to strengthen legal coherence, Sharīʿah governance, and alignment with maqāṣid al-sharīʿah.